Índices plaquetarios como predicción de Preeclampsia en gestantes del Hospital Belén de Trujillo en el periodo Octubre 2019 a Mayo 2020 - Marquezado Rivera, Mayra Isabel (2021)
Preeclampsia is a condition that remains as highly prevalent and with a high incidence rate in our settings. This raises the need for identifying the related factors to its prognostic. Moreover, the platelet indices account for the majority of hematological alterations in terms of frequency. Objective: Determine wether the platelet indices work as predictive factors for preeclampsia in pregnant women at Trujillo's Belen Hospital between October 2019 and May 2020. Methods: Analitical, observational, cross sectional, and diagnostic study was conducted in pregnant women at Trujillo's Belen Hospital between October 2019 and May 2020. Conclusions: Platelet indices work as predictive factors for pregnant women at Trujillo's Belen Hospital between October 2019 and May 2020.